2021
DOI: 10.3892/ijmm.2021.4906
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen disorders: Interpreting the abnormal regulation of aromatase in granulosa cells (Review)

Abstract: Ovarian granulosa cells (Gcs) are the most important source of estrogen. Therefore, aromatase (estrogen synthase), which is the key enzyme in estrogen synthesis, is not only an important factor of ovarian development, but also the key to estrogen secretion by Gcs. disorders of the ovarian estrogen secretion are more likely to induce female estrogen-dependent diseases and fertility issues, such as ovarian cancer and polycystic ovary syndrome. Hence, aromatase is an important drug target; treatment with its inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 95 publications
0
26
0
Order By: Relevance
“…Estradiol synthesis has been described as an energy-consuming process ( 2 ). Under hypoxia, energy mainly comes from glycolysis metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estradiol synthesis has been described as an energy-consuming process ( 2 ). Under hypoxia, energy mainly comes from glycolysis metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with oxidative phosphorylation, however, anaerobic glycolysis is significantly less efficient, providing a net production of only 2 ATP p er glucose molecule (versus 32 ATP per glucose molecule produced during oxidative phosphorylation) [30]. Since adenosine triphosphate (ATP) serves as an essential energy substrate and signaling molecule in FSH -mediated E2 synthesis [2], hypoxia seems to be detrimental for this process. Interestingly, when GCs were cultured under hypoxia, we observed no decrease in E2 production in FSH-treated cells.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in a similar case study, a population of Egyptian women with polycystic ovary syndrome, 53 patients and 53 controls in the rs4077582, were evaluated, which positively supported the occurrence of polymorphism and its association with PCOS [ 48 ]. In some research performed on the CYP11A1 promoter, It has been proposed that the regulation of the CYP11A1 promoter in granulosa cells is controlled by liver receptor homologue-1 (LRH-1) and Steroidogenic element-1 (SF-1) [ 49 ]. A 1999 study also supported this hypothesis, and it showed the loss of P450scc due to the knockout SF-1 [ 50 ].…”
Section: Cyp Genes and Pcos With Infertilitymentioning
confidence: 99%
“…The ovarian androgens are mainly androstenedione and T; androgen is the source of estrogen in the body, and granulosa cells (GCs) can aromatize T into estrogen [4]. Unlike T, DHT cannot be aromatized into estrogen [5], but it can increase the activity of aromatase in GCs [6].…”
Section: Introductionmentioning
confidence: 99%